A history of the global economy : from 1500 to the present - Baten, Joerg (Cambridge : Cambridge University Press, 2016)
Why are some parts of the world poor today, while others are rich? At which point in time did they diverge, and what were the reasons? These core questions are addressed in a concise and accessible introduction to global economic development since 1500. Leading economic historians from across the globe provide overviews of major world regions together with global comparison chapters and case studies highlighting key themes, individuals, processes and events. Utilising a set of common developmental indicators, the chapters address crucial issues such as how international trade and migration, institutions and flows of physical and human capital impacted economic growth. Richly illustrated with informative figures, maps, tables and charts, A History of the Global Economy summarises the key economic findings, debates and ideas, and provides students and the interested public with an up-to-date and engaging introduction to the origins and evolution of today's global economy.
Title from publisher's bibliographic system (viewed on 29 May 2018).
Keywords: elektronické knihy; electronic books; Economic history; Economic development -- History